Channels of financial sector development and rural-urban consumption inequality in India. Issue 12 (4th December 2017) - Mehta, Atul; Bhattacharya, Joysankar
Abstract : Purpose: The purpose of this paper is to examine the direct (microcredit), medium-direct (bank credit), and indirect (through economic growth) effect of financial sector development (FSD) on rural-urban consumption inequality (RUCI) in India using state-wise annual data from 1999-2000 to 2011-2012. Design/methodology/approach: A panel data analysis for a sample of 15 major Indian states using the generalized method of moments estimators provides an empirical evidence for the direct (microcredit), medium-direct (bank credit), and indirect (economic growth) effect of FSD on RUCI. Findings: FSD is pro-urban in India resulting in a declining rural-urban consumption ratio (RUCR) and increasing RUCI. The negative effect of FSD on RUCR is greatest through the medium-direct channel followed by the indirect and direct channels. Research limitations/implications: The study questions the social banking initiatives of the government in rural areas where more than 80 percent of the poor reside. There is a need for restructuring financial inclusion programs with a shift in their focus on rural areas and an improved mechanism to target the poor. Originality/value: The paper proposes that formal financial services by banks are primarily availed by non-poor and urban population and hence acts as a medium-direct channel whereas the semi-formal financial services by microfinance institutions specifically target the rural poor and act as a direct channel to affect the poor. It is the first ever study to use state-wise data on microcredit disbursed under Self-help Group Bank Linkage Program to assess the direct impact of FSD on RUCI.